2021
DOI: 10.1155/2021/6655417
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Molecular Nexus between GPCRs, ERS, and EMT

Abstract: G protein-coupled receptors (GPCRs) represent a large family of transmembrane proteins that transduce an external stimulus into a variety of cellular responses. They play a critical role in various pathological conditions in humans, including cancer, by regulating a number of key processes involved in tumor formation and progression. The epithelial-mesenchymal transition (EMT) is a fundamental process in promoting cancer cell invasion and tumor dissemination leading to metastasis, an often intractable state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 225 publications
(127 reference statements)
0
32
0
1
Order By: Relevance
“…These MMPs enhance motility by breaking down proteins in the basement membrane and extracellular matrix, to allow cells to metastasize away from the primary tumor. Recently, several types of the GPCR, protease-activated receptor (PAR), have been found to be upregulated in cancer [ 36 ]. Interestingly, the overexpression of PAR was found to induce EMT via TGF-β signaling, leading to the loss of cell polarity [ 37 ].…”
Section: Gpcr Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…These MMPs enhance motility by breaking down proteins in the basement membrane and extracellular matrix, to allow cells to metastasize away from the primary tumor. Recently, several types of the GPCR, protease-activated receptor (PAR), have been found to be upregulated in cancer [ 36 ]. Interestingly, the overexpression of PAR was found to induce EMT via TGF-β signaling, leading to the loss of cell polarity [ 37 ].…”
Section: Gpcr Signalingmentioning
confidence: 99%
“…While some of these mutations increased the agonist effect, others reduced or completely eliminated receptor activation, demonstrating how minute changes in the protein sequence can completely transform this GPCR’s capabilities. Recent work has also substantiated GPCRs’ role in the upregulation of EMT transcription factors, such as ZEB, Snail, and Twist, which are involved in numerous transitions, including cell polarity, cytoskeleton remodeling, migration, and invasion [ 36 , 40 ]. It has been challenging to delineate the actual function and various ligands of all GPCRs, due to their extensive crosstalk with the proteins and pathways that perform the vast majority of cellular functions.…”
Section: Gpcr Signalingmentioning
confidence: 99%
“…Recently, numerous researches have confirmed that EMT progression is mainly mediated by multiple key signal transduction pathways containing transforming growth factor-β (TGF-β)/Smads, Wnt/β-catenin, phosphatidylinositol 3-kinase (PI3K)/Akt, Notch, and NF-κB signaling pathways (De Rosa et al, 2015;Vinson et al, 2016;Mishra et al, 2017;Tan et al, 2017;Song et al, 2020). There are multiple specific EMTtranscription factors (EMT-TFs) involved in the EMT process undergoing tumor metastasis, including Snail, Slug (Snai2), ZEB1/2, and Twist (Goossens et al, 2017;Williams et al, 2019;Feng et al, 2020;Kumari et al, 2021;Lu et al, 2021), they closely acted pleiotropically and in diverse combinations to down-regulate epithelial marker E-cadherin, while upregulating the mesenchymal signatures such as N-cadherin, vimentin, and fibronectin, and thus promoting the tendency of cancer cells to mesenchymal-like features (Dongre and Weinberg, 2019), which ultimately contribute to the initiation of EMT process. The transcriptional modulation of multiple signal pathways with crosstalk molecular mechanisms closely involved in EMT regulation are summarized as indicated in Figure 1.…”
Section: Emt-related Signalings Involved In Metastasis Of Crc and Emt...mentioning
confidence: 96%
“…This topic was reviewed previously in [ 141 ]. EGFR is the most well-known growth factor receptor that interacts with G protein-coupled receptors (GPCRs) and is involved in the regulation of tumor development, invasion, and progression in a variety of malignancies [ 142 ].…”
Section: The Signaling Pathways In Metastasismentioning
confidence: 99%